2014
DOI: 10.1152/ajpregu.00260.2014
|View full text |Cite
|
Sign up to set email alerts
|

Reduced brown adipose tissue thermogenesis during environmental interactions in transgenic rats with ataxin-3-mediated ablation of hypothalamic orexin neurons

Abstract: Thermogenesis in brown adipose tissue (BAT) contributes to substantial increases in body temperature evoked by threatening or emotional stimuli. BAT thermogenesis also contributes to increases in body temperature that occur during active phases of the basic rest-activity cycle (BRAC), as part of normal daily life. Hypothalamic orexin-synthesizing neurons influence many physiological and behavioral variables, including BAT and body temperature. In conscious unrestrained animals maintained for 3 days in a quiet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 67 publications
1
31
1
Order By: Relevance
“…Our previous studies have shown that the integrated daily-life ultradian patterns are preserved in transgenic rats (Mohammed et al, 2014). The main difference between the rats and this study on mice is that the ultradian episodic increases in body temperature were almost absent in ORX-KO mice but not in the transgenic rats.…”
Section: Orexin-related Genetically Modified Animals For Ultradian Stcontrasting
confidence: 60%
See 4 more Smart Citations
“…Our previous studies have shown that the integrated daily-life ultradian patterns are preserved in transgenic rats (Mohammed et al, 2014). The main difference between the rats and this study on mice is that the ultradian episodic increases in body temperature were almost absent in ORX-KO mice but not in the transgenic rats.…”
Section: Orexin-related Genetically Modified Animals For Ultradian Stcontrasting
confidence: 60%
“…Our preliminary data shows that conditional ablation of orexin neurons attenuates the amplitude of ultradian pattern in metabolism in a time dependent manner (Ootsuka et al, 2014).…”
Section: Orexin-related Genetically Modified Animals For Ultradian Stmentioning
confidence: 73%
See 3 more Smart Citations